Do energy-saving nudges deliver during high-price periods? Field experimental evidence from the European energy crisis - Vicky Tinnefeld; Martin Kesternich; Madeline Werthschulte (ZEW - Leibniz-Zentrum für Europäische Wirtschaftsforschung, 2025)
Urged by the European Energy Crisis and the threatening consequences of severe natural gas shortages, energy providers launched gas-saving initiatives incorporating financial incentives to reduce residential natural gas consumption. In collaboration with one of Germany's largest energy providers, we conducted a natural field experiment (N = 2,598) to evaluate the effectiveness of a behaviorally-guided co-design of such a gas-saving initiative by implementing two established behavioral instruments - reminders of gas saving intentions and descriptive norm feedback. Our findings show limited effectiveness of the behavioural instruments during the high-price period. The feedback risks a "boomerang effect" among households with above-average initial savings, who reduce their conservation efforts in response. The reminder does not significantly enhance savings in our main specifications, yet, realizes 1 percentage point savings in alternate models refining for outliers. Potential mechanisms include a significant intention-action gap and misperceived effectiveness of energy-saving actions, which are not alleviated by the reminder.
Keywords: C93; D04; D91; Q41; 330; Residential energy savings; energy crisis; behavioral interventions; survey data; field experiment